Determination of potassium, sodium, and total alkalies in portland cement, fly ash, admixtures, and water of concrete by a simple flow injection flame photometric system - Jaroon Jakmunee (2018)
A simple flow injection with flame photometric detection has been developed for determination of sodium, potassium, and total alkalies in portland cement, fly ash, admixtures, and water of concrete. A liquid sample or a digest of solid sample was injected into a water carrier stream which flowed to a flame photometer. A change in emission intensity at a selected wavelength was recorded as a peak. An amplifier circuit was fabricated, which helped improve sensitivity of the flame photometer. Calibration graphs in the range of 0.05-1.0mg L-1and 1.0-20.0mg L-1were obtained with a detection limit of 0.02mg L-1, for both potassium and sodium determination. Relative standard deviations for 11 replicates of injecting of 10mg L-1potassium and sodium solutions were 1.69 and 1.79, respectively. Sample throughput of 120 h-1was achieved. The proposed method was successfully applied to portland cement, fly ash, admixtures, and water samples validated by the ASTM standard method and certified reference materials of portland cement. Copyright © 2011 Jaroon Junsomboon and Jaroon Jakmunee.